Genetic Evaluation and Application of Posterior Cranial Fossa Traits as Endophenotypes for Chiari Type I Malformation. (6th October 2013) - Markunas, Christina A.; Enterline, David S.; Dunlap, Kaitlyn; Soldano, Karen; Cope, Heidi; Stajich, Jeffrey; Grant, Gerald; Fuchs, Herbert; Gregory, Simon G.; Ashley‐Koch, Allison E.
Summary Chiari Type I Malformation (CMI) is characterized by herniation of the cerebellar tonsils through the base of the skull. Although cerebellar tonsillar herniation (CTH) is hypothesized to result from an underdeveloped posterior cranial fossa (PF), patients are frequently diagnosed by the extent of CTH without cranial morphometric assessment. We recently completed the largest CMI whole genome qualitative linkage screen to date. Despite an initial lack of statistical evidence, stratified analyses using clinical criteria to reduce heterogeneity resulted in a striking increase in evidence for linkage. The present study focused on the use of cranial base morphometrics to further dissect this heterogeneity and increase power to identify disease genes. We characterized the genetic contribution for a series of PF traits and evaluated the use of heritable, disease‐relevant PF traits in ordered subset analysis (OSA). Consistent with a genetic hypothesis for CMI, much of the PF morphology was found to be heritable and multiple genomic regions were strongly implicated from OSA, including regions on Chromosomes 1 (LOD = 3.07, p = 3 × 10−3) and 22 (LOD = 3.45, p = 6 × 10−5) containing several candidates warranting further investigation. This study underscores the genetic heterogeneity of CMI and the utility of PF traits in CMI genetic studies.